Staff Development to Enhance the Value of Educational Institutions in the Digital Era - Sirisuk, Patcharin; Jareonsri, Srisakul (Ratchaphruek Journal, 2025)
This study aims to explore concepts and strategies for staff development in the digital era where educators must learn alongside their digital-native students. The study is structured into four key sections. The first section examines the transformation of school organizations in response to digital advancements providing a comprehensive understanding of the broader changes in education. The second section focuses on technological skill development for teachers emphasizing the necessity of digital competency in modern education. The third section discusses staff development as a means to enhance the value of educational institutions presenting both learning processes and competency-building strategies to strengthen school effectiveness The final section introduces learning models and development approaches tailored for teachers in the digital era aligning with contemporary human resource development trends. Key strategies discussed include re-skilling which equips educators with new skills to meet evolving job demands, and up-skilling which enhances existing skills to improve professional competency the 70-20-10 learning model which is a well-established framework emphasizing experience-based social and formal learning e-learning and social media integration which leverage digital platforms for continuous learning blended learning which combines online and face-to-face instruction for optimal learning outcomes and learning for change which fosters adaptability to dynamic work environments and evolving job roles. These strategies collectively support the sustainability of educational standards at both institutional and international levels ensuring that schools remain competitive and effective in a rapidly evolving digital society.